"She had the occupation of singer": the Rio de Janeiro Music Conservatory and female professionalization in sacred environment (1853-1873) (Orfeu, 2024)
Work was part of the daily lives of more than half of the women who lived in Rio de Janeiro during the 19th century. The objectives of this research are to analyze the impact of the creation of the class of Rudiments and Singing for the Female Sex and of Singing at the Conservatory of Music on the training and professionalization of women in sacred environment during the years 1853 to 1873 and to analyze their social networks and their connection with class entities. Using as references Edward Thompson, Claude Dubar and Jean Sirinelli, using as sources periodicals from the Digital Hemeroteca of the National Library, institutional documents, records from the Familysearch website and recent studies, it is concluded that this institution promoted professional training for women from less privileged classes, allowing them to work as singers in churches, occupy leadership positions in the Devotion of Santa Cecilia, developing a professional and personal identity, as well as social relationships mediated by Christian principles, obtaining, in addition to their subsistence, visibility and social status.
Keywords: Rio de Janeiro Music Conservatory; Rio de Janeiro in the 19th century; working women in music; Religious festivities; devotion of Saint Cecilia